2005
DOI: 10.1021/es048464a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Degradation Pathways in an Aquifer with Mixed Chlorinated Hydrocarbon Contamination Using Stable Isotope Analysis

Abstract: The demonstration of monitored natural attenuation (MNA) of chlorinated hydrocarbons in groundwater is typically conducted through the evaluation of concentration trends and parent−daughter product relationships along prevailing groundwater flow paths. Unfortunately, at sites contaminated by mixtures of chlorinated ethenes, ethanes, and methanes, the evaluation of MNA by using solely concentration data and parent−daughter relationships can result in erroneous conclusions regarding the degradation mechanisms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 29 publications
3
79
0
Order By: Relevance
“…For 1,2-DCA, it was demonstrated that two aerobic biodegradation pathways lead to significantly different carbon isotope fractionation Aravena, 2000, Hirschorn et al, 2004). Furthermore, Hunkeler et al (2005) and Hirschorn et al (2007) demonstrated the use of stable carbon isotope ratios to differentiate chlorinated ethene (TCE, DCE and VC) production by reductive dechlorination of PCE from production by dehydrochlorination (b-dehaloelimination) of 1,1,2,2-tetrachloroethane, 1,1,2-trichloroethane and 1,2-dichloroethane, and to differentiate ethane production by reductive dechlorination of VC from dehydrochlorination of 1,2-DCA. Lojkasek-Lima et al (2012) used CSIA data to verify that biotic degradation of TCE as well as abiotic degradation by Fe(0) occurred at a Fe(0) reactive wall in a TCE plume.…”
Section: Introductionmentioning
confidence: 99%
“…For 1,2-DCA, it was demonstrated that two aerobic biodegradation pathways lead to significantly different carbon isotope fractionation Aravena, 2000, Hirschorn et al, 2004). Furthermore, Hunkeler et al (2005) and Hirschorn et al (2007) demonstrated the use of stable carbon isotope ratios to differentiate chlorinated ethene (TCE, DCE and VC) production by reductive dechlorination of PCE from production by dehydrochlorination (b-dehaloelimination) of 1,1,2,2-tetrachloroethane, 1,1,2-trichloroethane and 1,2-dichloroethane, and to differentiate ethane production by reductive dechlorination of VC from dehydrochlorination of 1,2-DCA. Lojkasek-Lima et al (2012) used CSIA data to verify that biotic degradation of TCE as well as abiotic degradation by Fe(0) occurred at a Fe(0) reactive wall in a TCE plume.…”
Section: Introductionmentioning
confidence: 99%
“…Biotic and abiotic degradations of chlorinated ethenes and ethanes have been documented by compound specific isotope analysis (CSIA) in several studies (for chlorinated ethenes e.g. Courbet et al, 2011;Hunkeler et al, 2005;Lollar et al, 2001 and for chlorinated ethanes e.g. Lollar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Usually intrinsic biodegradation by indigenous microbial populations is the key process for contaminant elimination and methods are required to demonstrate its efficacy. In groundwater studies, compound-specific isotope analysis (CSIA) has been used increasingly to demonstrate in situ biodegradation of various types of organic contaminants (Kelley et al, 1997;Sturchio et al, 1998;Hunkeler et al, 1999;Sherwood Lollar et al, 2001;Kolhatkar et al, 2002;Mancini et al, 2002;Meckenstock et al, 2002;Song et al, 2002;Kirtland et al, 2003;Richnow et al, 2003a,b;Chu et al, 2004;Griebler et al, 2004;Steinbach et al, 2004;Hunkeler et al, 2005;Morrill et al, 2005). In contrast, only a few studies have investigated the use of CSIA in the unsaturated zone (Stehmeier et al, 1999;Kirtland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%